Hubungan Penggunaan KB Suntik 3 Bulan Dengan Kenaikan Berat Badan Pada Wanita Usia Subur Di Puskesmas Maga Kabupaten Mandailing Natal Tahun 2022 - Dewi Purba; Basaria Manurung (Pusat Riset dan Inovasi Nasional, 2023)
Injectable contraception is a way to prevent pregnancy by means of hormonal injections. This type of hormonal contraceptive injection in Indonesia is being used more and more because it works effectively, is practical to use, is relatively cheap and safe. This study aims to determine the relationship between the use of 3-month injection birth control and weight gain in women of childbearing age at the Maga Health Center in Mandailing Natal Regency in 2022. This type of research is an analytical survey with a cross-sectional approach. The population is all pregnant women who are at the Maga Health Center, Mandailing Natal Regency in 2022, with a total of 36 pregnant women. The number of samples used was 52 people obtained by using purposive sampling technique. Data analysis technique using chi square. the results obtained in this study were from 52 respondents, there was a relationship between the knowledge variable and weight gain with a value of p = 0.001, there was a relationship between the variable length of use and weight gain with a value of p = 0.002, there was a relationship between the age variable and weight gain body with a value of p = 0.002, there is a relationship between the education variable and weight gain with a value of p = 0.003 and there is a relationship between the work variable and weight gain with a value of p = 0.001. there is a relationship between knowledge variables and weight gain, there is a relationship between variables of length of use and weight gain, there is a relationship between age variables and weight gain, there is a relationship between education variables and weight gain and there is a relationship between work variables and weight gain . It is suggested to the puskesmas to increase the mother's knowledge to increase counseling related to the use of injecting contraception.